Prevalence and Diversity of Staphylococcus aureus and Staphylococcal Enterotoxins in Raw Milk From Northern Portugal - Oliveira, Ricardo; Pinho, Eva; Almeida, Gonçalo; Azevedo, Nuno F.; Almeida, Carina (Frontiers in Microbiology, 2022)
Staphylococcus aureus and staphylococcal enterotoxins are a serious public health concern associated with hospital and community-acquired illnesses. Dairy animals frequently shed S. aureus into the milk supply which can lead to food poisoning in humans. This study aims to investigate the prevalence and genetic diversity of S. aureus and staphylococcal enterotoxins in raw milk from the main dairy region of mainland Portugal. S. aureus was found in 53.0% (95% CI: 40.6–65.4%) of 100 raw cow’s milk samples collected from bulk cooling tanks. The highest contamination level was 3.4 log10 CFU.mL–1, and in some samples more than one S. aureus strain was identified. Staphylococcal enterotoxins (SEA-SEE) were detected in one sample. Spa typing revealed 62 distinct S. aureus isolates, being t529 (17.7%, 95% CI: 8.2–27.3%) and t1403 (16.1%, 95% CI: 7.0–25.3%) the predominant types, commonly associated with livestock infection or carriage. The antimicrobial susceptibility test showed that 35.5% of the S. aureus isolates were resistant to at least one antimicrobial agent, with resistance to penicillin being the highest (32.3%, 95% CI: 20.6–43.9%) followed by tetracycline (24.2%, 95% CI: 13.5–34.9%), ciprofloxacin (16.1%, 95% CI: 7.0–25.3%) and chloramphenicol (16.1%, 95% CI: 7.0–25.3%). Moreover, five isolates (8.1%, 95% CI: 1.3–14.8%) were identified as methicillin-resistant S. aureus (MRSA, cefoxitin resistant). Regarding virulence/resistance genes, 46,8% (95% CI: 34.4–59.2%) isolates harbored at least one enterotoxin-encoding gene, and the seg gene was the most frequently detected (41.9%, 95% CI: 29.7–54.2%) followed by the sei (40.3%, 95% CI: 28.1–52.5%), sec (6.5%, 95% CI: 0.3–12.6%), seh (4.8%, 95% CI: 0.0–10.2%), and sea (1.6%, 95% CI: 0.0–4.7%) genes. Five (8.1%, 95% CI: 1.3–14.8%) non-enterotoxigenic isolates carried the mecA gene (corresponding to isolates phenotypically classified as MRSA), and 4.8% (95% CI: 0.0–10.2%) enterotoxigenic strains also had the tsst-1 gene. Our study confirm that raw milk can be a zoonotic source of S. aureus, including enterotoxigenic and MRSA strains. Furthermore, the majority of enterotoxigenic isolates were found to contain genes encoding SEs (SEG, SEH and SEI) not routinely screened. This shows the need for a broader SE screening in food safety control, as well as the relevance of risk mitigation measures to control S. aureus transmission along the food chain in Portugal.